Retrospective study of dermatophylosis in sheep in the Sertão of Paraíba - Garcia, Dlean da Silva; de Oliveira , Flaviane Neri Lima; de Souto , Erick Platiní Ferreira; Wanderley , Vitória Dantas; de Oliveira, Artefio Martins; Dantas, Antonio Flávio Medeiros (Seven Editora, 2024)
The epidemiological, clinical and pathological aspects of dermatophylosis in sheep in the Sertão da Paraíba, Northeast Brazil, are described. From 2003 to 2023, 7 cases of dermatophylosis in sheep were diagnosed at the Animal Pathology Laboratory of the Federal University of Campina Grande. Of the affected animals, four were females and three males. Most of the animals were adults, four of whom were crossbred and three of the Santa Inês breed. The disease was most frequently diagnosed in April, followed by June and November. All the animals came from municipalities belonging to the Sertão region of Paraíba. Clinically, the animals presented multifocal to coalescent areas of alopecia, located in decreasing order of frequency, on the head, back, neck, ears and limbs. In two animals, the lesions were generalized. Macroscopically, the prevalent skin lesions were characterized by thickening of the skin by slightly moist crusts that formed grayish-white plaques. Histologically, multifocal to coalescent areas of epidermal hyperplasia (acanthosis) were observed, associated with marked parakeratotic and/or orthokeratotic hyperkeratosis. In the middle of the epidermis and between the keratin lamellae, multifocal areas of moderate neutrophilic infiltrate associated with cellular debris (intraepidermal pustules and serocellular crusts, respectively) and numerous filamentous, segmented and basophilic structures, compatible with D. congolensis, were observed. The diagnosis was established through epidemiological, clinical and anatomopathological findings. The disease occurs sporadically in sheep in the Sertão da Paraíba, affecting adult animals of both sexes, and characterized by alopecic and crusty skin lesions. DOI:https://doi.org/10.56238/sevened2024.023-019